HOW FINANCIAL DIGITALIZATION LINKS FINANCIAL BEHAVIOR, FINANCIAL ATTITUDES, AND INFORMATION TECHNOLOGY TO SME PERFORMANCE - Sri Hermuningsih; Erri Kurniawati Widodo; Riskin Hidayat; Saizal Bin Pinjaman (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2026)
This research was conducted to analyze the influence of financial behavior, financial attitudes and information technology on the performance of food MSMEs in the Yogyakarta Special Region with financial digitalization as a mediating variable. The subjects of this research were food MSME actors in the Special Region of Yogyakarta with a sampling technique using purposive sampling so that the number of respondents in this research was 140 respondents. The method used in this research is descriptive quantitative with the analytical tools used are SPSS ver.26 and SmartPls ver.4 and data collection for this research uses a questionnaire. The results of this research indicate that Financial Behavior has a significant positive influence on the performance of food MSMEs in the province of D.I. Yogyakarta, Financial Attitudes have a significant positive influence on the performance of MSMEs, Information technology has a significant positive influence on the performance of MSMEs, Financial Digitalization has a significant positive influence on the performance of MSMEs, while Financial Behavior through financial digitalization has a significant positive influence on the performance of MSMEs, then Financial Attitudes through Financial digitalization does not have a significant positive influence on MSME performance, and Information Technology through financial digitalization has a significant positive influence on MSME performance.